Identity and otherness in Forrest Gump: a close-up into twentieth-century America - Feneja, Fernanda Luísa da Silva, 1964- (2014)
Forrest Gump’s life experience spans a few decades of the second half of the twentieth century. Major events in American history, encompassed by the social and cultural setting of the times, are displayed through the main character’s particular angle, a first-person narrative where fact and fiction, History and stories are inextricably interwoven. While Forrest’s unique view of the world is shaped by his mental and physical limitations, he embodies oddity and otherness as seen from other people’s eyes. However, whether because of his choices or merely out of chance, his difference seems to consistently bring him to the core of mainstream American values and dreams. This article aims to reflect on this peculiar relationship between man and contemporaneity, focusing primarily on the dichotomy identity/alterity, both in terms of individual development and within the realm of American experience. The interrelation of both concepts in the film further enables the discussion on how criticism of American culture and history, on the one hand, and allegiance to it, on the other, may correlate, thereby contributing to enlarge the reflection on the meaning of Forrest Gump.